Small mammal communities at high altitude within the Sneeuberg Mountain complex, Eastern Cape Province, South Africa - Kok, Armand du Preez (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
Due to their widespread and specious nature, small mammals are ideal for biogeographical studies. Small mammals also effectively connect various trophic levels by being both consumers and prey items for other animals. The Great Escarpment is the dominant mountain landscape in South Africa. Yet, very little small mammal research has been conducted on the Great Escarpment outside of the Main Drakensberg Mountains. This is surprising given the importance of mountains in shaping regional ecology. In this study, I assessed the diversity and community composition of small mammals at three high altitude (>1700m) sites within the Sneeuberg Mountain Complex (SMC) from June 2009 to May 2010. I also tested the effectiveness of five different bait types for measuring small mammal diversity (i.e. number of individuals caught, species richness, Shannon diversity index and Simpson index of diversity). Out of a total of 423 captures, 292 individuals of 12 small mammal species (one shrew, one elephant shrew and 10 rodents) were recorded over 5280 trap nights. The species richness and diversity of small mammals captured at the three sites were similar and this homogeneity was probably related to the regional processes (e.g. climate and latitude) that govern species richness and diversity. The most effective bait type in terms of capture success, species richness and diversity measurements was peanut butter and oats. In addition, the use of richness estimators revealed that peanut butter and oats was the most effective bait for sampling the species richness of small mammals. The effectiveness of peanut butter and oats was related to this bait having a more attractive scent, when compared to the other bait types. Future studies should focus on researching the range of local and regional processes that drive small mammal diversity at high altitudes in South Africa. I also recommend the use of more than one bait type when planning to survey small mammal communities.
Keywords: Mountain animals -- Research -- South Africa -- Eastern Cape; Mammal populations -- Research -- South Africa -- Eastern Cape; Mammals -- Research -- South Africa -- Eastern Cape